Edaphoclimatic Descriptors of Wild Tomato Species (Solanum Sect. Lycopersicon) and Closely Related Species (Solanum Sect. Juglandifolia and Sect. Lycopersicoides) in South America - Ramírez-Ojeda, Gabriela; Peralta, Iris Edith; Rodríguez-Guzmán, Eduardo; Sahagún-Castellanos, Jaime; Chávez-Servia, José Luis; Medina-Hinostroza, Tulio Cecilio; Rijalba-Vela, Jorge Rodrigo; Vásquez-Núñez, Leopoldo Pompeyo; Rodríguez-Pérez, Juan Enrique (Frontiers in Genetics, 2021)
Wild species related to cultivated tomato are essential genetic resources in breeding programs focused on food security to face future challenges. Ecogeographic analysis allow to identify species adaptive ranges and most relevant environmental variables explaining their patterns of actual distribution. This information is relevant for the rescue, conservation, genetic characterization, documentation and use of wild tomatoes and close related species. The objective of this research was to identify edaphoclimatic descriptors and statistical relationship of climatic and edaphic variables of 4,649 accessions of 12 wild tomato species classified in Solanum sect. Lycopersicon and clustered into 4 phylogenetic groups: “Lycopersicon group” (S. pimpinellifolium, S. cheesmaniae, S. galapagense), “Arcanum group” (S. arcanum, S. chmielewskii S. neorickii), “Eriopersicon group” (S. habrochaites, S. huaylasense, S. corneliomulleri, S. peruvianum, S. chilense), “Neolycopersicon group” (S. pennellii); and 2 phylogenetically related groups in Solanum sect. Juglandifolia with two species (S. juglandifolium and S. ochranthum), and in Section Lycopersicoides including S. lycopersicoides and S. sitiens. Relationship between climate and soil variables were determined by canonical correlation analysis. Statistics were performed with 21 climatic variables (19 bioclimatic variables from WorldClim, annual evapotranspiration and altitude), and 14 edaphic variables (pH, CEC, SB, CO, CaCO3, CaSO4, salinity, sodicity, percentage of lime, clay, sand and gravel, bulk density, TEB) in raster format with spatial resolution of 900 m. Ecogeographic analysis revealed the most important edapho-climatic descriptors that are useful to understand wild species distribution and environmental adaptive patterns in South America. This approach has promissory applications for biodiversity conservation and uses of valuable genetic resources related to a leading crop.